Bochdaleck hernia and pulmonary sequestration: case report of an unusual association - Andrea C. de Souza-Contenças; Andrey Cabral-Paes; Márcio L. Duarte; Lucas Ribeiro-dos Santos; Mayara Oliveira-da Silva; Marcelo de Queiroz-P (Publicaciones Permanyer, 2024)
Introduction: Although bochdalek hernia is the most common type of congenital diaphragmatic hernia, it is still a rare condition. It can be complicated by the development of secondary pulmonary sequestration, which is subdivided into intralobar pulmonary sequestration and extralobar pulmonary sequestration. Case report: This study describes a case of pulmonary sequestration due to bochdalek hernia in a one-year-old girl, who underwent surgical correction. Discussion: Pulmonary sequestration can be confused with other more frequent pathologies, such as pneumonia or tumors, and diagnosis can be facilitated through the use of vascular imaging techniques, which confirm the diagnosis and show the vascularization of the hernia content.